Improving the Quality and Content of Sweet Potato (Ipomoea batatas L.) by Adding Chlorine - Emir Rasyid Annaufal; Aisar Novita; Mohammad Shahid B Shahrun (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2025)
Sweet potato (Ipomoea batatas L.) is a food commodity with significant potential as an alternative source of carbohydrates. However, damage caused by microbial contamination and quality degradation during storage remains a significant challenge. This study aimed to evaluate the effect of chlorine treatment on sweet potato quality. Chlorine treatment was performed by soaking sweet potatoes in a sodium hypochlorite (NaOCl) solution at a specified concentration for a set duration. Parameters assessed included microbial contamination levels, changes in skin and flesh color, water content, and shelf life. The results demonstrated that chlorine treatment significantly reduced surface microbial populations and slowed the rate of physiological deterioration during storage. Furthermore, chlorination did not adversely affect the physical appearance or organoleptic qualities of the sweet potatoes. Therefore, chlorine treatment can be an effective method for handling sweet potatoes, extending their shelf life and maintaining product quality.